That is not my house? Household renters’ flood preparedness intention in the East Coast Region of Malaysia - Mohd Rozaimy, Ridzuan; Jamal Rizal, Razali; Ju, Soon-Yew; Noor Amira Syazwani, Abd Rahman (IDRiM Society, 2024)
By integrating the Theory of Planned Behavior (TPB) and the Health Belief Model (HBM), this study examines factors influencing flood preparedness intention among household renters in the East Coast Region of Malaysia. The study utilized purposive sampling, involving the collection of data from 150 household renters residing in the East Coast Region of Malaysia through an online survey. The collected data were then analyzed using Structural Equation Modeling (SEM) with Smart Partial Least Squares (SmartPLS). The results revealed that past experience (PE) was positively associated with both perceived severity (SEV) and susceptibility (SUC). However, both SEV and SUC were not correlated with attitude (ATT). Among the three determinants originating from TPB, only ATT was found to be correlated with flood preparedness intention (INT). It is worthy to notify that trust in public protection (TPP) played a moderating effect on the relationship between ATT and INT. The findings will offer valuable insights for policymakers, renters, landlords, and community rganizations to develop targeted interventions and bolster flood preparedness among household renters in the East Coast region, ultimately fostering resilience and mitigating the impact of future flood events. Besides that, this study provides firsthand information on the predictors of flood preparedness behaviour among household renters in the East Coast Region, Peninsular Malaysia.